Interleukin-37 reduces lipopolysaccharide induced matrix metalloproteinase-9 in gingival epithelial cells - Arzu Beklen; Muhammet Burak Yavuz; Deniz Uckan (BMC Oral Health)
Abstract Background In periodontal diseases, the recognition of pathogen-associated molecular patterns (PAMPs) triggers signaling cascades that lead to the release of matrix metalloproteinases (MMPs). Interleukin-37 (IL-37) is recognized as a key suppressor of the immune response. This study aimed to detect the expression and distribution of IL-37 in gingival tissues and analyze its suppressor role in MMP-9 in response to lipopolysaccharide (LPS)-stimulated gingival epithelial cells. Methods Immunohistochemistry localized IL-37 in gingival tissues from periodontitis patients and healthy controls (N = 10). The induction of IL-37 expression by LPS was analyzed using the conditioned medium of gingival epithelial cells through enzyme-linked immunosorbent assay (ELISA). To determine the relevant MMP-9 levels in epithelial cells following exposure to LPS alone or in combination with IL-37, both quantitative PCR (qPCR) and enzyme-linked immunosorbent assay (ELISA) were performed. Results Cultured epithelial cells secreted significantly higher levels of IL-37 when stimulated with LPS compared to unstimulated controls. Both ELISA and qPCR showed that LPS stimulation significantly increased MMP-9 levels. However, co-culture with IL-37 markedly reduced LPS-induced MMP-9 expression at both the protein and mRNA levels. Furthermore, immunohistochemistry revealed increased IL-37 expression in periodontitis tissues, both in epithelial cells and connective tissue. Conclusions Gingival epithelial cells may contribute to tissue responses in periodontitis through the secretion of MMP-9 in response to PAMPs. Furthermore, IL-37 appears to have a potential role in modulating and reducing this response, as observed in the decreased MMP-9 expression following IL-37 co-stimulation.